Voice and Property: Latinos, White Conservatives, and Urban Renewal in 1960s San Francisco. Issue 3 (August 2014) - Contreras, Eduardo
Abstract: San Francisco's Mission District residents marshaled divergent perspectives on urban renewal in the 1960s shaped by class, race, and differences over liberalism. Latinos and their allies in a low-income minority coalition backed redevelopment if allowed to control the program. Middle-class white conservatives opposed it because it threatened their economic interests. The community's crusade ultimately resulted in triumph and endurance, not disappointment and deracination.